2011
DOI: 10.1103/physrevb.84.054455
|View full text |Cite
|
Sign up to set email alerts
|

Frustration-driven magnetic order in hexagonal InMnO3

Abstract: InMnO 3 is a peculiar member of the hexagonal manganites h-RMnO 3 (where R is a rare-earth metal element), showing crystalline, electronic, and magnetic properties at variance with the other compounds of the family. We have studied high quality samples synthesized at high pressure and temperature by powder neutron diffraction. The position of the Mn ions is found to be close to the threshold x = 1/3 where superexchange Mn-Mn interactions along the c axis compensate. Magnetic long-range order occurs below T N =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…In contrast to other hexagonal RMnO 3 , the magnetic order below causes a doubling of the unit cell along the -axis [89]. High resolution neutron scattering experiments are consistent with the doubling of the magnetic unit cell, the onset of magnetic order at 120 K, and the absence of any further spin reorientation at lower temperatures [204]. The magnetic symmetry of the ordered Mn 3+ spins was determined to be either Γ 2 or Γ 4 (Figure 4), with the spins of two subsequent unit cells along the -axis reversed by 180 ∘ .…”
Section: Inmnosupporting
confidence: 48%
See 2 more Smart Citations
“…In contrast to other hexagonal RMnO 3 , the magnetic order below causes a doubling of the unit cell along the -axis [89]. High resolution neutron scattering experiments are consistent with the doubling of the magnetic unit cell, the onset of magnetic order at 120 K, and the absence of any further spin reorientation at lower temperatures [204]. The magnetic symmetry of the ordered Mn 3+ spins was determined to be either Γ 2 or Γ 4 (Figure 4), with the spins of two subsequent unit cells along the -axis reversed by 180 ∘ .…”
Section: Inmnosupporting
confidence: 48%
“…The lattice parameters of InMnO 3 , as determined from X-ray and neutron scattering experiments [89,200,204], deviate significantly from other hexagonal RMnO 3 . While the lattice parameter of all hexagonal RMnO 3 , including ScMnO 3 , are a linear function of the 3+ ionic radius, and of InMnO 3 deviate significantly with and found to be clearly smaller and larger, respectively, as expected from the linear dependence [89].…”
Section: Inmnomentioning
confidence: 99%
See 1 more Smart Citation
“…From heat capacity measurements Tachibana et al 10 have observed for the critical exponent α = − 0.16, whereas Katsufuji et al 11 have obtained α = 0.25 from dielectric susceptibility measurements. For ν Fabreges et al 12 reported the value of 0.65.…”
Section: Introductionmentioning
confidence: 95%
“…[21][22][23] Nevertheless this study was only a zeroth order approximation to this type of systems as manganese compounds are known to display low magnetic anisotropy. In fact experimental data for several manganese compounds [40][41][42] have shown that these compounds are well described by the Heisenberg model. Consequently, the model of Ref.…”
Section: Introductionmentioning
confidence: 99%